Data transmission in Hybrid Distributed Environment - Anton Pavlovich Teykhrib (Institute of Advanced Engineering and Science, 2016)
This article discusses a hybrid distributed environment including two levels of nodes: the first level which has high quality channels between the nodes, and the second one in which the nodes are directly involved in communication and the communication is performed through the first-level nodes. For the indicated distribution scheme, the questions of selection of the best path between the first-level nodes are solved based on such communication channel characteristics as delay in packet transmission, jitter in transmission, packet loss in transmission, and choosing a method for data transmission through the selected best path: protocols of transport and network layers have been compared, and the use of network layer has been preferred.